O papel dos sistemas visual, vestibular, somatosensorial e auditivo para o controle postural - Kleiner, Ana Francisca Rozin [UNESP]; De Camargo Schlittler, Diana Xavier [UNESP]; Del Rosário Sánchez-Arias, Mónica [UNESP] (My University, 2011)
The maintenance of a given body orientation is obtained by the complex relation between sensory information and muscle activity. Therefore, this study purpose was to review the role of visual, somatosensory, vestibular and auditory information in the maintenance and control of the posture. Method. a search by papers for the last 24 years was done in the PubMed and CAPES databases. The following keywords were used: postural control, sensory information, vestibular system, visual system, somatosensory system, auditory system and haptic system. Results. the influence of each sensory system and its integration were analyzed for the maintenance and control of the posture. Conclusion. the literature showed that there is information redundancy provided by sensory channels. Thus, the central nervous system chooses the main source for the posture control.
The role of visual, vestibular, somatosensory and auditory systems for the postural control
Keywords: Nervous System; Posture; Sense Organs; body posture; central nervous system; homeostasis; human; Medline; review; sensorimotor integration; somatosensory system; tactile discrimination; vestibular system; visual system